Application of graph theory in the energy efficient architectural design - Bolgarova, Natalia (KNUCA, 2015)
Energy-efficient house is considered as a structure consisting of individual elements (volumes). To analyze their relationships with the architectural design of objects suggested to use one of the methods section of mathematics – graph theory. There are basic principles of the theory, which can be used to generate functional and spatial structure of the energy-efficientbuilding.
Применение теории графов в строительном проектировании
Keywords: graph theory; energy efficient; construction design; geometric model; теория графов; энергоэффективная архитектура; структура архитектурного объекта; проектирование; геометрическая модель